Impact of Domestic Violence on Psycho-social Wellbeing of Women in Bukhalu Sub-county, Bulambuli District - Lydia Zesiro (Uganda Christian University, 2025)
This research report study based on the impact of domestic violence on psycho-social wellbeing of women in Bukhalu Sub-County, Bulambuli District and it was guided by the following research objectives: to find out how physical violence affects psycho-social wellbeing of women in Bukhalu Sub County, Bulambuli district, to assess how sexual violence affects psycho-social wellbeing of women in Bukhalu Sub County, Bulambuli district and to examine interventions for preventing domestic violence and promote psycho-social wellbeing of women in Bukhalu Sub County, Bulambuli district. The study used a descriptive research design in form of questionnaire‟s; it considered a population of 195 respondents with a sample size of 131 respondents. Findings indicated exposure to acts of violence is a stressful event that has negative effects on women‟s psychological wellbeing, findings indicated that exposure to acts of violence is a stressful event that has negative effects on women‟s psychological wellbeing and lastly findings indicated that Counseling of both individuals and groups can work as a measure for preventing domestic violence. The study concluded that exposure to acts of violence is a stressful event that has negative effects on women‟s psychological, that violence can negatively affect factors that improve psychological wellbeing and lastly that Violence can result in to disability which leaves permanent emotions and psychological tortures. This research report recommended that there should be more investments by different Governments in a number of strategies to ensure prevent domestic violence.